Kesan belok ke kiri semasa merah terhadap kapasiti persimpangan berlampu isyarat - Ismail Abdul Rahman, (1996)
This paper discusses the increase in capacity of the approach road and signallised junction with the implementation of left turn during red. The factors that influenced the effectiveness of this strategy are also discussed in addition to the steps undertaken in estimating the actual capacity obtained with the implementation of this strategy. Data obtained from the study site was analysed manually and using the Signalized Intersection Capacity Analysis and Highway Capacity softwares. Results of analyses indicated that the increase in approach capacity of up to 15.8% and the total junction capacity of 5.4% were obtained with the implementation of this strategy